2019
DOI: 10.1096/fj.201900922r
|View full text |Cite
|
Sign up to set email alerts
|

Different monocyte phenotypes result in proresolving macrophages in conjugated linoleic acid‐induced attenuated progression and regression of atherosclerosis

Abstract: Monocytes/macrophages drive progression and regression of atherosclerosis. Conjugated linoleic acid (CLA), an anti‐inflammatory lipid, mediates atheroprotective effects. We investigated how CLA alters monocyte/macrophage phenotype during attenuated progression and regression of atherosclerosis. Apolipoprotein E knockout (ApoE−/−) mice were fed a high‐fat (60%) high‐cholesterol (1%) diet (HFHCD) for 2 wk, followed by 6‐wk 1% CLA 80: 20 supplementation to investigate disease progression. Simultaneously, ApoE−/− … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…CLA, a pro-resolving lipid mediator, has previously been shown to attenuate progression and induce regression of atherosclerosis via regulation of monocyte function and phenotype (3)(4)(5). However, the molecular mechanisms underlying the atheroprotective effect of CLA have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CLA, a pro-resolving lipid mediator, has previously been shown to attenuate progression and induce regression of atherosclerosis via regulation of monocyte function and phenotype (3)(4)(5). However, the molecular mechanisms underlying the atheroprotective effect of CLA have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…ApoE −/− mice fed a 1% cholesterol chow diet (1% CD) or normal chow diet (ND) group were used as controls. ApoE −/− mice were randomized at 40 days to receive either a ND for 12 weeks, a 1% CD for 12 weeks or a 1% CD for 12 weeks where the final 4 weeks were supplemented with 1% CLA blend (1% CD + CLA) to induce regression (3)(4)(5).…”
Section: Animals and Dietsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent experimental study, Bruen et al showed that conjugated linoleic acid (CLA), which is an antiinflammatory lipid, can induce regression of atherosclerosis in ApoE -/mice. In mice fed CLA, more monocytes differentiated into anti-inflammatory M2 macrophages [30]. Sun et al fed ApoE -/model mice phenytoin, a non-selective voltage-gated sodium channels antagonist, and the mice subsequently exhibited increased levels of anti-inflammatory monocytes and decreased levels of proinflammatory monocytes [31].…”
Section: Database Analysismentioning
confidence: 99%